Implementation of the Polar Code: Functional Requirements Regulating Ship Operations in Polar Waters - Espen Engtrø; Ove Tobias Gudmestad; Ove Njå (Arctic Review on Law and Politics, 2020)
In 2017, the The International Code for Ships Operating in Polar Waters (Polar Code) – a set of function-based regulations applicable to Arctic and Antarctic waters, with the goal of increasing awareness and improving safety for ship operations in polar waters – entered into force. This article examines the Polar Code’s contribution to the establishment of new standards and guidelines, with the problem under discussion being the extent to which the function-based regulations contribute to enhancing safety for ship operations in the Arctic, given that maritime activities in these waters are associated with great risks and uncertainties. The article gives a historical review, elucidating the background leading to the development of the Polar Code, followed by a review of the structure and key principles of the regulations. Further, ship traffic in the Arctic region and those subject to the Polar Code are examined, followed by a summary of findings and experiences from three survival exercises (SARex I, II and III), performed in northern areas around Svalbard between 2016 and 2018. The article concludes that safe ship operations depend on those subject to the regulations conducting thorough operational risk assessments that cover all potential hazards, in order to mitigate sufficiently. Further, the presence of authorities is found to be crucial, with validation of the adequacy and the dimensioning of the implemented measures being of the essence.